Ly6CLo Monocyte/Macrophages are Essential for Thrombus Resolution in a Murine Model of Venous Thrombosis - Kimball, Andrew Scott; Obi, Andrea Tara; Luke, Catherine E.; Dowling, Abigail R.; Cai, Qing; Adili, Reheman; Jankowski, Hannah; Schaller, Matthew; Holinstadt, Michael; Jaffer, Farouc A.; Kunkel, Steven L.; Gallagher, Katherine A.; Henke, Peter K. (Thrombosis and Haemostasis, 2020)
Venous thrombosis (VT) resolution is a complex process, resembling sterile wound healing. Infiltrating blood-derived monocyte/macrophages (Mo/MΦs) are essential for the regulation of inflammation in tissue repair. These cells differentiate into inflammatory (CD11b+Ly6CHi) or proreparative (CD11b+Ly6CLo) subtypes. Previous studies have shown that infiltrating Mo/MΦs are important for VT resolution, but the precise roles of different Mo/MΦs subsets are not well understood. Utilizing murine models of stasis and stenosis inferior vena cava thrombosis in concert with a Mo/MΦ depletion model (CD11b-diphtheria toxin receptor [DTR]-expressing mice), we examined the effect of Mo/MΦ depletion on thrombogenesis and VT resolution. In the setting of an 80 to 90% reduction in circulating CD11b+Mo/MΦs, we demonstrated that Mo/MΦs are not essential for thrombogenesis, with no difference in thrombus size, neutrophil recruitment, or neutrophil extracellular traps found. Conversely, CD11b+Mo/MΦ are essential for VT resolution. Diphtheria toxoid (DTx)-mediated depletion after thrombus creation depleted primarily CD11b+Ly6CLo Mo/MΦs and resulted in larger thrombi. DTx-mediated depletion did not alter CD11b+Ly6CHi Mo/MΦ recruitment, suggesting a protective effect of CD11b+Ly6CLo Mo/MΦs in VT resolution. Confirmatory Mo/MΦ depletion with clodronate lysosomes showed a similar phenotype, with failure to resolve VT. Adoptive transfer of CD11b+Ly6CLo Mo/MΦs into Mo/MΦ-depleted mice reversed the phenotype, restoring normal thrombus resolution. These findings suggest that CD11b+Ly6CLo Mo/MΦs are essential for normal VT resolution, consistent with the known proreparative function of this subset, and that further study of Mo/MΦ subsets may identify targets for immunomodulation to accelerate and improve thrombosis resolution.
Keywords: venous thromboembolism; thrombosis; macrophages; monocytes; inflammation